Pengaruh Orientasi Kewirausahaan, Inovasi Produk dan Keunggulan Bersaing Terhadap Kinerja Pemasaran UMKM Kuliner di Kota Bandar Lampung - Tri Lestira Putri Warganegara; Karliony Ardila (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study is to explore the relationship between entrepreneurial orientation, product innovation, competitive advantage, and marketing performance of culinary micro-, small- and medium-sized enterprises (MSMEs) in Bandar Lampung. The study sample consisted of 53 of his MSME culinary entrepreneurs from Bandar Lampung city. The approach used in this study is quantitative research techniques and data analysis using IBM SPSS Statistics26. The results of the subtest show that while competitive advantage has a positive impact on marketing performance, it has no significant impact on business alignment or product innovation. Moreover, concurrent testing shows that marketing performance is jointly influenced by business alignment, product innovation, and competitive advantage. These results provide culinary SME entrepreneurs in Bandar Lampung with key insights to improve their marketing performance. Enhancing competitive advantage can be a powerful strategy for increasing business competitiveness, but the importance of business alignment and product innovation is also considered in achieving more optimal marketing outcomes. As business competition becomes more and more intense, this research could be the basis for strategic decisions in the development and growth of Bandar Lampung's culinary SME business.